Process for removing sulfur dioxide from lithium mica sintering flue gas
Patent Information
- Application Number
- CN202510966396.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-14
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-07-14
AI Technical Summary
然而,这一过程不可避免地产生大量烟气,其中二氧化硫是主要污染物之一
[0013]有益效果: (1)脱硫效率显著提升:双层吸附机制:静电团聚(效率>90%)与袋式过滤(效率>95%)协同作用,系统总脱硫效率达98.3%-99.2%。纳米纤维改性:丙烯酸甲酯接枝的PVDC纤维比表面积提升3.2倍,SO2吸附容量达135mg/g(传统CaO吸附剂仅28mg/g)。
Smart Images

Figure CN120771670B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of modified nanomaterials technology, specifically, it relates to a process for removing sulfur dioxide from sintering flue gas of lithium mica. Background Technology
[0002] Lepidolite is a lithium-containing silicate mineral, and its abundant lithium content makes it an important raw material in the new energy field (such as lithium battery manufacturing). In the extraction process of lepidolite, sintering is a crucial step used to release lithium from the mineral structure. However, this process inevitably generates a large amount of flue gas, of which sulfur dioxide is one of the main pollutants. Sulfur dioxide not only contributes to acid rain and air pollution but also damages the respiratory system. Therefore, how to efficiently remove SO2 from the sintering flue gas of lepidolite has become an important issue for promoting the sustainable development of lithium resources.
[0003] Traditional sulfur dioxide removal technologies mainly include wet desulfurization and dry desulfurization. Wet desulfurization (such as the limestone-gypsum method) is widely used due to its high desulfurization efficiency, but its disadvantages include equipment susceptibility to corrosion, generation of large amounts of wastewater, and high operating costs. In contrast, dry desulfurization (such as the spray adsorbent method) is simple to operate and generates no wastewater, but the utilization rate of the desulfurizing agent is low, and the desulfurization efficiency is difficult to meet the requirements of high-concentration SO2 flue gas. These traditional methods face additional challenges when treating lepidolite sintering flue gas because this flue gas is characterized by high temperature, high humidity, and complex composition.
[0004] In recent years, the development of nanomaterials technology has provided new ideas for gas purification. Modified nanomaterials, due to their high specific surface area, excellent adsorption performance, and tunable surface chemistry, have shown great potential in the field of SO2 removal. For example, the adsorption and catalytic conversion capabilities of nano-oxides can be significantly improved by surface modification or doping with transition metals. Studies by Liu et al. (Liu, Y., et al. (2018). Enhanced SO2 adsorption performance of transition metal-modified nano-TiO2. Journal of Hazardous Materials, 350, 1-10.) showed that the adsorption capacity of transition metal-loaded nano-TiO2 for SO2 far exceeds that of unmodified materials. Furthermore, Wang et al. (Wang, X., et al. (2020). High-temperature catalytic removal of SO2 over CeO2 / MgOnanocomposites. Applied Catalysis B: Environmental, 265, 118565.) developed a nano-CeO2 / MgO composite material that can catalyze the conversion of SO2 to sulfate at high temperatures, achieving efficient desulfurization. These studies provide a theoretical basis for the process design of this invention.
[0005] In view of the characteristics of sintering flue gas from lepidolite, this invention proposes a sulfur dioxide removal process based on modified nanomaterials, aiming to overcome the limitations of traditional methods, achieve efficient and stable removal of SO2, and reduce environmental impact and operating costs. Summary of the Invention
[0006] Problem to be solved: During the sintering of lepidolite, the flue gas contains a high concentration of sulfur dioxide (SO2), a gas harmful to the environment and human health. With the increasing demand for lithium resources in new energy fields (such as lithium battery manufacturing), the development and utilization of lepidolite has gradually become a research hotspot. However, existing technologies face many problems and limitations in treating sulfur dioxide in lepidolite sintering flue gas, urgently requiring an efficient, environmentally friendly, and economical technical solution to address these shortcomings. This invention aims to propose improvements to address the following specific problems: Wet desulfurization (such as the limestone-gypsum method) is currently a commonly used industrial method for SO2 removal, with a high desulfurization efficiency of over 90%. However, this method has significant drawbacks when treating lepidolite sintering flue gas: Severe equipment corrosion: Acidic components in the flue gas (such as SO2) react with the aqueous solution used in the wet system to generate sulfuric acid, leading to corrosion of the reactor and pipelines, increasing maintenance costs. Wastewater generation: Wet desulfurization generates a large amount of sulfate-containing wastewater. Treating this wastewater requires additional facilities and costs, and improper treatment may cause secondary pollution. High operating costs: Wet processes require a continuous supply of raw materials such as limestone and the treatment of byproducts (such as gypsum), resulting in high overall operating costs. Dry desulfurization (such as the spray adsorbent method) has the advantage of simple operation because it does not require water treatment, but it performs poorly in the treatment of lepidolite sintering flue gas: Low desulfurizing agent utilization: The adsorbents (such as CaO or MgO) used in traditional dry desulfurization have large particles and limited specific surface area, resulting in low contact efficiency with SO2 and insufficient utilization of the desulfurizing agent. Limited desulfurization efficiency: For high-concentration SO2 flue gas, the removal efficiency of dry desulfurization is usually lower than that of wet processes, which cannot meet strict environmental emission standards. Poor adaptability: Lepidolite sintering flue gas has the characteristics of high temperature, high humidity and complex composition, and traditional dry desulfurizing agents are difficult to maintain stable desulfurization performance under such conditions. Compared to other industrial flue gases, lepidolite sintering flue gas possesses unique physicochemical properties, posing additional challenges to existing desulfurization technologies: High-temperature and high-humidity environment: Sintering flue gas temperatures typically range from 200-500℃, with high humidity. Under these conditions, traditional desulfurization methods either experience reduced efficiency or equipment damage. Complex composition: In addition to SO2, the flue gas may contain dust, volatile compounds, and other acidic gases, increasing the complexity of the desulfurization process. Stability requirements: Existing technologies struggle to continuously and efficiently remove SO2 in this dynamically changing environment. Currently used desulfurizing agents (such as limestone or calcium oxide) are mostly disposable consumables, lacking effective regeneration methods, leading to: Resource waste: The desulfurizing agents cannot be recycled, increasing raw material consumption. High operating costs: Frequent replacement of desulfurizing agents results in poor process economics, especially when treating large-scale lepidolite sintering flue gas, where cost issues are particularly prominent.To address the aforementioned problems, this invention proposes a sulfur dioxide removal process based on modified nanomaterials, aiming to achieve the following objectives: Improved desulfurization efficiency: By utilizing the high specific surface area and strong adsorption capacity of modified nanomaterials, highly efficient SO2 removal is ensured under high temperature and humidity conditions, achieving a desulfurization efficiency of over 95%. Enhanced process stability: A desulfurizing agent suitable for the complex composition of lepidolite sintering flue gas is developed, ensuring stable adsorption and catalytic performance in high temperature and humidity environments. Renewability of the desulfurizing agent: Through thermal or chemical regeneration methods, the desulfurizing agent can be recycled, thereby reducing raw material consumption and operating costs. Avoidance of secondary pollution: The dry desulfurization process avoids wastewater generation, reduces environmental impact, and achieves a green and environmentally friendly desulfurization process. Simplified operation and improved economic efficiency: A desulfurization process easily applicable to industrial applications is designed, reducing equipment corrosion and improving overall economic benefits. Technical solution
[0007] To solve the above problems, the present invention adopts the following technical solution.
[0008] A process for removing sulfur dioxide from sintering flue gas of lepidolite includes the following steps: 40-65 parts by weight of sodium bicarbonate, 15-30 parts by weight of slaked lime (CAS: 1305-62-0), 5-12 parts by weight of lithium sulfate, and 10-30 parts by weight of polyvinylidene chloride fiber are mixed evenly to obtain an adsorbent; then, the prepared adsorbent is injected into an electrostatic agglomerator at a temperature of 120-160℃ to co-agglomerate and adsorb fly ash particles in the sintering flue gas of lepidolite; next, the flue gas after co-agglomeration and adsorption is passed through a bag filter to adsorb residual sulfur dioxide; finally, the adsorbent after co-agglomeration and adsorption is regenerated to obtain a regenerated adsorbent for recycling.
[0009] The process for removing sulfur dioxide from lepidolite sintering flue gas includes the following steps: 45-60 parts by weight of sodium bicarbonate, 20-28 parts by weight of slaked lime, 5-12 parts by weight of lithium sulfate, and 12-25 parts by weight of polyvinylidene chloride fiber are mixed evenly to obtain an adsorbent; then, the prepared adsorbent is injected into an electrostatic agglomerator at a temperature of 130-150℃ to co-agglomerate and adsorb fly ash particles in the lepidolite sintering flue gas; next, the flue gas after co-agglomeration and adsorption is passed through a bag filter to adsorb residual sulfur dioxide; finally, the adsorbent after co-agglomeration and adsorption is regenerated to obtain a regenerated adsorbent for recycling.
[0010] The process for removing sulfur dioxide from lepidolite sintering flue gas includes the following steps: 55 parts by weight of sodium bicarbonate, 24 parts by weight of slaked lime, 10 parts by weight of lithium sulfate, and 20 parts by weight of polyvinylidene chloride fiber are mixed evenly to obtain an adsorbent; then, the prepared adsorbent is injected into an electrostatic agglomerator at a temperature of 140°C to co-agglomerate and adsorb with fly ash particles in the lepidolite sintering flue gas; next, the flue gas after co-agglomeration and adsorption is passed through a bag filter to adsorb residual sulfur dioxide; finally, the adsorbent after co-agglomeration and adsorption is regenerated to obtain a regenerated adsorbent for recycling.
[0011] The physicochemical parameters of the polyvinylidene chloride fiber (CAS No.: 9002-85-1) are as follows: glass transition temperature: -17℃, melting temperature: 205℃, crystal density: 1.96g / cm³, fiber diameter: 0.1mm, fiber length: 2mm. The modification method of polyvinylidene chloride (PVDC) fiber is as follows: PVDC fiber is dispersed in 15-30 times its mass of acetone at 60-70℃ and 120-140 rpm. Then, 2-3 times the mass of PVDC fiber of methyl acrylate (CAS: 96-33-3) and 0.2-0.7 times the mass of PVDC fiber of glycidyl methacrylate (CAS: 106-91-2) are added. The mixture is stirred and mixed at 80-90℃ for 24 hours. Then, 0.05-0.15% of the mass of PVDC fiber of ammonium persulfate is added. Under nitrogen protection, the temperature is raised to 85±2℃, and the stirring rate is maintained at 150 rpm for 30 minutes. Finally, 0.5-1.2% of the mass of PVDC fiber of triethylamine (CAS No.: 121-44-8) is added, and the reaction is carried out at 120-140℃ for 2-4 hours. After cooling, the product is obtained. The parameters for the co-condensation are as follows: the adsorbent is injected via high-pressure jet, with a pressure of 0.5-1.0 MPa, and the pressure source is high-pressure gas. The parameters for the co-condensation are: voltage: 30-40 kV, current: 0.1-0.3 mA / m. 2 Residence time: 1.5-2 seconds. The internal relative humidity of the electrostatic agglomerator is 10-20%. The regeneration process is as follows: the first stage temperature control is 450℃-480℃, maintained for 20-30 minutes; the second stage temperature control is 500℃-520℃, maintained for 15-20 minutes; the third stage temperature control is 465℃, maintained for 10-15 minutes.
[0012] For the electrostatic agglomeration system, the core equipment is a high-voltage electrostatic agglomerator with an operating voltage of 30-40kV (the IZS42 series electrostatic eliminator supports ±6kV voltage), a temperature range of 120-160℃, and a humidity control range of 10-20%RH. The supporting equipment is the SMCIZS42-CG series electrostatic eliminator (dual AC mode, maximum load current 100mA). For the bag filter system, the model is the Liefert LFD series multi-bag filter, LFD-2-9P type: capacity: 270t / h, filtration area: 4.5m². 2 Applicable pressure: 0.5MPa; frame material: galvanized steel; filter media: glass fiber / activated carbon composite material. For the high-pressure injection device: Graco Finex 289353 model; maximum working pressure: 1.0MPa; nozzle type: air-assisted. For the regeneration heating system: three-stage temperature-controlled regeneration furnace; temperature gradient: 450℃→520℃→465℃; temperature control accuracy: ±5℃; heat source type: electric heating (ZH-65 steam generator). For monitoring instruments: electrostatic detection, IZS31-DF feedback sensor; detection distance: 10-50mm; communication protocol: NPN / PNP output; flow control: Liefert DN200 dual filter; interface standard: HG / T20592 flange; pressure rating: PN16.
[0013] Beneficial effects: (1) Significantly improved desulfurization efficiency: Dual-layer adsorption mechanism: electrostatic agglomeration (efficiency > 90%) and bag filtration (efficiency > 95%) work synergistically, and the total desulfurization efficiency of the system reaches 98.3%-99.2%. Nanofiber modification: PVDC fibers grafted with methyl acrylate have a 3.2-fold increase in specific surface area and an SO2 adsorption capacity of 135 mg / g (compared to only 28 mg / g for traditional CaO adsorbent).
[0014] (2) Significantly reduced operating costs: Regeneration and recycling system: Three-stage temperature-controlled regeneration technology (450-520℃) allows the adsorbent to be recycled 20-25 times, reducing raw material consumption by 65%-72%; Energy consumption optimization: The electrostatic agglomerator operates at 140℃ (traditional activated carbon desulfurization requires 130-150℃), reducing energy consumption by 18%.
[0015] (3) Outstanding environmental friendliness: Zero wastewater discharge: The dry process avoids the acidic wastewater generated by wet desulfurization (the wastewater treatment cost of traditional process is >8 yuan / ton); By-product resource utilization: The SO2 concentration recovered in the regeneration process is >15% (vol), which can be directly used for sulfuric acid preparation.
[0016] (4) Enhanced process stability: resistance to complex working conditions: modified fibers maintain stable adsorption at 10-20% humidity (the efficiency of traditional activated carbon decreases by more than 40% in high humidity environment); extended equipment life: fiberglass pipes (temperature resistance >200℃) replace stainless steel, reducing corrosion rate by 90%. Attached Figure Description
[0017] Figure 1 This is a color change diagram of the adsorbent before and after the regeneration treatment in Example 5 of this invention.
[0018] Figure 2 This is a scanning electron microscope image of the polyvinylidene chloride fiber prepared in Example 5 of this invention. Detailed Implementation
[0019] The present invention will be further described below with reference to specific embodiments.
[0020] Unless otherwise defined, the technical and scientific terms used in the following embodiments have the same meanings as commonly understood by one of ordinary skill in the art to which this invention pertains. In practical applications, the parts by weight involved in this invention may be set in kilograms. Example
[0021] The process for removing sulfur dioxide from lepidolite sintering flue gas includes the following steps: 405 parts by weight of sodium bicarbonate, 15 parts by weight of slaked lime, 5 parts by weight of lithium sulfate, and 10 parts by weight of polyvinylidene chloride fiber are mixed evenly to obtain an adsorbent; then, the prepared adsorbent is injected into an electrostatic agglomerator at 120°C to co-agglomerate and adsorb with fly ash particles in the lepidolite sintering flue gas; next, the flue gas after co-agglomeration and adsorption is passed through a bag filter to adsorb residual sulfur dioxide; finally, the adsorbent after co-agglomeration and adsorption is regenerated to obtain a regenerated adsorbent for recycling.
[0022] The physicochemical parameters of the polyvinylidene chloride (PVDC) fiber are as follows: glass transition temperature: -17℃, melting temperature: 205℃, crystal density: 1.96 g / cm³, fiber diameter: 0.1 mm, and fiber length: 2 mm. The modification method of the PVDC fiber is as follows: PVDC fiber is dispersed in acetone at 60℃ and 120 rpm in 15 times its mass. Then, methyl acrylate (2 times its mass) and glycidyl methacrylate (0.2 times its mass) are added. The mixture is stirred at 80℃ for 24 hours. Next, ammonium persulfate (0.05% by mass) of PVDC fiber is added. Under nitrogen protection, the temperature is raised to 85±2℃, and the stirring rate is maintained at 150 rpm for 30 minutes. Finally, triethylamine (0.5% by mass) of PVDC fiber is added, and the reaction is carried out at 120℃ for 2 hours. After cooling, the product is obtained. The parameters for the co-condensation are as follows: the adsorbent is injected via high-pressure jet at a pressure of 0.5 MPa, and the pressure source is high-pressure gas. The specific parameters for the co-condensation are: voltage: 30 kV, current: 0.1 mA / m. 2 Residence time: 1.5s. The internal relative humidity of the electrostatic agglomerator is 10%. The regeneration process is as follows: first stage temperature control at 450℃, maintained for 20 minutes; second stage temperature control at 500℃, maintained for 15 minutes; third stage temperature control at 465℃, maintained for 10 minutes. Example
[0023] The process for removing sulfur dioxide from lepidolite sintering flue gas includes the following steps: 65 parts by weight of sodium bicarbonate, 30 parts by weight of slaked lime, 12 parts by weight of lithium sulfate, and 30 parts by weight of polyvinylidene chloride fiber are mixed evenly to obtain an adsorbent; then, the prepared adsorbent is injected into an electrostatic agglomerator at 160°C to co-agglomerate and adsorb fly ash particles in the lepidolite sintering flue gas; next, the flue gas after co-agglomeration and adsorption is passed through a bag filter to adsorb residual sulfur dioxide; finally, the adsorbent after co-agglomeration and adsorption is regenerated to obtain a regenerated adsorbent for recycling.
[0024] The physicochemical parameters of the polyvinylidene chloride (PVDC) fiber are as follows: glass transition temperature: -17℃, melting temperature: 205℃, crystal density: 1.96 g / cm³, fiber diameter: 0.1 mm, and fiber length: 2 mm. The modification method of the PVDC fiber is as follows: PVDC fiber is dispersed in acetone at 70℃ and 140 rpm in 30 times its mass. Then, methyl acrylate (3 times its mass) and glycidyl methacrylate (0.7 times its mass) are added. The mixture is stirred at 90℃ for 24 hours. Next, ammonium persulfate (0.15% by mass of PVDC fiber) is added. Under nitrogen protection, the temperature is raised to 85±2℃, and the stirring rate is maintained at 150 rpm for 30 minutes. Finally, triethylamine (1.2% by mass of PVDC fiber) is added, and the reaction is carried out at 140℃ for 4 hours. After cooling, the product is obtained. The parameters for the co-condensation are as follows: the adsorbent is injected via high-pressure jet at a pressure of 1.0 MPa, and the pressure source is high-pressure gas. The specific parameters for the co-condensation are: voltage: 40 kV, current: 0.3 mA / m. 2 Residence time: 2s. The internal relative humidity of the electrostatic agglomerator is 20%. The regeneration process is as follows: the first stage temperature control is 480℃, maintained for 30 minutes; the second stage temperature control is 520℃, maintained for 20 minutes; the third stage temperature control is 465℃, maintained for 15 minutes. Example
[0025] The process for removing sulfur dioxide from lepidolite sintering flue gas includes the following steps: 45 parts by weight of sodium bicarbonate, 20 parts by weight of slaked lime, 5 parts by weight of lithium sulfate, and 12 parts by weight of polyvinylidene chloride fiber are mixed evenly to obtain an adsorbent; then, the prepared adsorbent is injected into an electrostatic agglomerator at 130°C to co-agglomerate and adsorb fly ash particles in the lepidolite sintering flue gas; next, the flue gas after co-agglomeration and adsorption is passed through a bag filter to adsorb residual sulfur dioxide; finally, the adsorbent after co-agglomeration and adsorption is regenerated to obtain a regenerated adsorbent for recycling.
[0026] The physicochemical parameters of the polyvinylidene chloride (PVDC) fiber are as follows: glass transition temperature: -17℃, melting temperature: 205℃, crystal density: 1.96 g / cm³, fiber diameter: 0.1 mm, and fiber length: 2 mm. The modification method of the PVDC fiber is as follows: PVDC fiber is dispersed in acetone at 60℃ and 120 rpm in 15 times its mass. Then, methyl acrylate (2 times its mass) and glycidyl methacrylate (0.2 times its mass) are added. The mixture is stirred at 80℃ for 24 hours. Next, ammonium persulfate (0.05% by mass) of PVDC fiber is added. Under nitrogen protection, the temperature is raised to 85±2℃, and the stirring rate is maintained at 150 rpm for 30 minutes. Finally, triethylamine (0.5% by mass) of PVDC fiber is added, and the reaction is carried out at 120℃ for 2 hours. After cooling, the product is obtained.
[0027] The parameters for the co-condensation are as follows: the adsorbent is injected via high-pressure jet at a pressure of 0.5 MPa, and the pressure source is high-pressure gas. The specific parameters for the co-condensation are: voltage: 30 kV, current: 0.1 mA / m. 2 Residence time: 1.5s. The internal relative humidity of the electrostatic agglomerator is 10%. The regeneration process is as follows: first stage temperature control at 450℃, maintained for 20 minutes; second stage temperature control at 500℃, maintained for 15 minutes; third stage temperature control at 465℃, maintained for 10 minutes. Example
[0028] The process for removing sulfur dioxide from lepidolite sintering flue gas includes the following steps: 60 parts by weight of sodium bicarbonate, 28 parts by weight of slaked lime, 12 parts by weight of lithium sulfate, and 25 parts by weight of polyvinylidene chloride fiber are mixed evenly to obtain an adsorbent; then, the prepared adsorbent is injected into an electrostatic agglomerator at 150°C to co-agglomerate and adsorb fly ash particles in the lepidolite sintering flue gas; next, the flue gas after co-agglomeration and adsorption is passed through a bag filter to adsorb residual sulfur dioxide; finally, the adsorbent after co-agglomeration and adsorption is regenerated to obtain a regenerated adsorbent for recycling.
[0029] The physicochemical parameters of the polyvinylidene chloride (PVDC) fiber are as follows: glass transition temperature: -17℃, melting temperature: 205℃, crystal density: 1.96 g / cm³, fiber diameter: 0.1 mm, and fiber length: 2 mm. The modification method of the PVDC fiber is as follows: PVDC fiber is dispersed in acetone at 70℃ and 140 rpm in 30 times its mass. Then, methyl acrylate (3 times its mass) and glycidyl methacrylate (0.7 times its mass) are added. The mixture is stirred at 90℃ for 24 hours. Next, ammonium persulfate (0.15% by mass of PVDC fiber) is added. Under nitrogen protection, the temperature is raised to 85±2℃, and the stirring rate is maintained at 150 rpm for 30 minutes. Finally, triethylamine (1.2% by mass of PVDC fiber) is added, and the reaction is carried out at 140℃ for 4 hours. After cooling, the product is obtained.
[0030] The parameters for the co-condensation are as follows: the adsorbent is injected via high-pressure jet at a pressure of 1.0 MPa, and the pressure source is high-pressure gas. The specific parameters for the co-condensation are: voltage: 40 kV, current: 0.3 mA / m. 2 Residence time: 2s. The internal relative humidity of the electrostatic agglomerator is 20%. The regeneration process is as follows: the first stage temperature control is 480℃, maintained for 30 minutes; the second stage temperature control is 520℃, maintained for 20 minutes; the third stage temperature control is 465℃, maintained for 15 minutes. Example
[0031] The process for removing sulfur dioxide from lepidolite sintering flue gas includes the following steps: 55 parts by weight of sodium bicarbonate, 24 parts by weight of slaked lime, 10 parts by weight of lithium sulfate, and 20 parts by weight of polyvinylidene chloride fiber are mixed evenly to obtain an adsorbent; then, the prepared adsorbent is injected into an electrostatic agglomerator at a temperature of 140°C to co-agglomerate and adsorb with fly ash particles in the lepidolite sintering flue gas; next, the flue gas after co-agglomeration and adsorption is passed through a bag filter to adsorb residual sulfur dioxide; finally, the adsorbent after co-agglomeration and adsorption is regenerated to obtain a regenerated adsorbent for recycling.
[0032] The physicochemical parameters of the polyvinylidene chloride (PVDC) fiber are as follows: glass transition temperature: -17℃, melting temperature: 205℃, crystal density: 1.96 g / cm³, fiber diameter: 0.1 mm, and fiber length: 2 mm. The modification method of the PVDC fiber is as follows: PVDC fiber is dispersed in acetone at 65℃ and 130 rpm in 24 times its mass. Then, methyl acrylate (2.5 times its mass) and glycidyl methacrylate (0.5 times its mass) are added. The mixture is stirred at 85℃ for 24 hours. Next, ammonium persulfate (0.1% by mass) of the PVDC fiber is added. Under nitrogen protection, the temperature is raised to 85±2℃, and the stirring rate is maintained at 150 rpm for 30 minutes. Finally, triethylamine (0.8% by mass) of the PVDC fiber is added, and the reaction is carried out at 130℃ for 3 hours. After cooling, the product is obtained.
[0033] The parameters for the co-condensation are as follows: the adsorbent is injected via high-pressure jet at a pressure of 0.8 MPa, and the pressure source is high-pressure gas. The specific parameters for the co-condensation are: voltage: 35 kV, current: 0.2 mA / m. 2 Residence time: 1.8s. The internal relative humidity of the electrostatic agglomerator is 15%. The regeneration process is as follows: first stage temperature control at 470℃, maintained for 25 minutes; second stage temperature control at 510℃, maintained for 18 minutes; third stage temperature control at 465℃, maintained for 13 minutes.
[0034] Comparative Example 1 Traditional wet desulfurization: The limestone-gypsum desulfurization process is adopted, using limestone slurry with a mass concentration of 20% to circulate and spray in the spray tower, with a liquid-to-gas ratio of 15L / m³. After the flue gas temperature drops to 50℃, it is discharged through a demister.
[0035] Comparative Example 2 Conventional dry desulfurization: Pure calcium oxide powder (200 mesh) is used as the adsorbent and is injected into the 160℃ flue gas duct via pneumatic conveying. No electrostatic agglomeration device is installed. Parameters: Ca / S molar ratio 2.5:1, residence time 2s, adsorbent for single use.
[0036] Comparative Example 3 Electrostatic agglomeration-free process: The adsorbent formulation of Example 5 is used, but the electrostatic agglomerator is eliminated and the gas is directly processed through a bag filter. Parameters: injection pressure 0.5MPa, flue gas residence time shortened to 0.8s.
[0037] Comparative Example 4 Unmodified fiber: Ordinary polyvinylidene chloride fiber without methyl acrylate modification was used, and other components were the same as in Example 3. Parameters: Fiber specific surface area was reduced to 12 m² / g, and glass transition temperature was increased to -5°C.
[0038] Comparative Example 5 Lithium sulfate component missing: Remove lithium sulfate from the adsorbent and adjust the mass percentage to 60% sodium bicarbonate, 30% quicklime, and 10% polyvinylidene chloride fiber.
[0039] Comparative Example 6 Single-stage regeneration process: The adsorbent formulation of Example 4 was used, but the regeneration treatment was changed to a single stage of 520°C maintained for 60 minutes, and temperature gradient control was not implemented.
[0040] Comparative Example 7 High-pressure injection exceeding limits: Maintain the component ratio of Example 2 and increase the injection pressure to 1.5 MPa.
[0041] Comparative Example 8 Humidity runaway condition: Based on the process in Example 1, humidity control is removed, and the humidity of the flue gas flues naturally.
[0042] Test Plan Flue gas conditions: Simulated sintering flue gas from lithium mica, SO2 concentration 2000 mg / Nm³, temperature 150℃, humidity 18%. Adsorbent dosage: Adsorbent to flue gas mass ratio 1:1000. Number of cycles: The adsorbent was regenerated and recycled 20 times to evaluate the desulfurization efficiency decay. Operating time: Each test lasted 24 hours, recording the SO2 mass percentage removal rate, adsorbent consumption, and energy consumption.
[0043] Test Results: Example 1: Desulfurization efficiency: Initial 95.2%, 93.8% after 20 cycles. Adsorbent consumption: 0.8 kg per ton of flue gas. Energy consumption: Electrostatic agglomeration energy consumption 12 kWh / t of flue gas. Example 2: Desulfurization efficiency: Initial 98.5%, 97.2% after 20 cycles. Adsorbent consumption: 0.6 kg per ton of flue gas. Energy consumption: Electrostatic agglomeration energy consumption 15 kWh / t of flue gas. Example 3: Desulfurization efficiency: Initial 96.0%, 94.5% after 20 cycles. Adsorbent consumption: 0.75 kg per ton of flue gas. Energy consumption: Electrostatic agglomeration energy consumption 13 kWh / t of flue gas. Example 4: Desulfurization efficiency: Initial 98.0%, 96.8% after 20 cycles. Adsorbent consumption: 0.65 kg per ton of flue gas. Energy consumption: Electrostatic agglomeration energy consumption 14 kWh / t of flue gas. Example 5: Desulfurization efficiency: initial 99.2%, 98.3% after 20 cycles. Adsorbent consumption: 0.5 kg per ton of flue gas. Energy consumption: electrostatic agglomeration energy consumption 11 kWh / t of flue gas; in addition, such as Figure 1The diagrams shown illustrate the effects of adsorbent treatment. Comparative Example 1: Desulfurization efficiency: 92.5%. Operating cost: RMB 12 per ton of flue gas (including wastewater treatment). Equipment corrosion: Annual maintenance costs account for 15% of total costs. Comparative Example 2: Desulfurization efficiency: 78.6%. Adsorbent consumption: 2.5 kg per ton of flue gas. Energy consumption: Low energy consumption due to no electrostatic agglomeration, but insufficient efficiency. Comparative Example 3: Desulfurization efficiency: 85.4%. Adsorbent consumption: 1.2 kg per ton of flue gas. Energy consumption: Increased pressure drop in the bag filter, energy consumption 15 kWh / t of flue gas. Comparative Example 4: Desulfurization efficiency: 88.2%. Adsorbent consumption: 1.0 kg per ton of flue gas. Cycling performance: Efficiency drops to 75% after 10 cycles. Comparative Example 5: Desulfurization efficiency: 90.1%. Adsorbent consumption: 0.9 kg per ton of flue gas. Regeneration effect: Efficiency drops to 80% after 15 cycles. Comparative Example 6: Desulfurization efficiency: Initially 96.5%, decreasing to 85% after 10 cycles. Adsorbent consumption: 0.8 kg per ton of flue gas. Incomplete regeneration: Sulfate residues on the adsorbent surface. Comparative Example 7: Desulfurization efficiency: 97.0%, but excessively high injection pressure led to uneven adsorbent dispersion. Energy consumption: Energy consumption of the injection system increased by 20%. Comparative Example 8: Desulfurization efficiency: Efficiency decreased to 90% when humidity fluctuated. Adsorbent agglomeration: Affected recycling. Results analysis: Analysis of Examples 1-5 showed that the desulfurization efficiency was above 95%, and the efficiency decay was less than 1.5% after 20 cycles. Example 5 performed best: Initial desulfurization efficiency was 99.2%, still reaching 98.3% after 20 cycles. Adsorbent consumption was the lowest (0.5 kg / t flue gas), and energy consumption was only 11 kWh / t flue gas. Optimized ratio, three-stage regeneration, and electrostatic agglomeration technology significantly improved efficiency and recycling performance. Analysis of Comparative Examples 1-8: Comparative Example 1 (wet method): efficiency 92.5%, but high cost and severe corrosion. Comparative Example 2 (dry method): efficiency only 78.6%, high adsorbent consumption. Comparative Example 3: efficiency drops to 85.4% without electrostatic agglomeration, increased energy consumption. Comparative Example 4: unmodified fibers lead to decreased efficiency and cycle performance. Comparative Example 5: lack of lithium sulfate reduces regeneration effect. Comparative Example 6: single-stage regeneration cannot fully restore adsorbent activity. Comparative Example 7: excessive high-pressure injection increases energy consumption without improving effect. Comparative Example 8: uncontrolled humidity leads to efficiency fluctuations and adsorbent agglomeration. This invention achieves efficient, stable, and low-cost SO2 removal through a dual adsorption mechanism of modified nanofibers, electrostatic agglomeration, and bag filtration, combined with three-stage temperature-controlled regeneration technology. Compared with traditional methods: desulfurization efficiency is increased to over 95% (optimal 99.2%). Operating costs are reduced by 65%. The adsorbent can be recycled more than 20 times. The test results fully demonstrate the significant technical advantages and economic benefits of this invention, making it suitable for lithium mica sintering flue gas treatment scenarios.
[0044] For modified polyvinylidene chloride (PVDC) fibers, the swelling pretreatment stage involves using acetone as a polar solvent to swell the fibers through permeation, disrupting the hydrogen bond network between molecular chains and creating channels for subsequent monomer penetration. Temperature control within the 60-70℃ range accelerates the swelling process while preventing fiber thermal decomposition (melting temperature 205℃). Mechanical dispersion is achieved at 120-140 rpm, promoting uniform fiber dispersion and achieving monofilament separation, increasing the specific surface area to 3.2 times the initial value. Monomer grafting reaction follows: Grafting mechanism: Under free radical initiation, methyl acrylate monomers bind to free radical sites on the fiber surface through C=C double bond breakage, forming long side-chain structures. Effects: The introduction of carboxylic acid ester groups (-COOR) enhances the chemical adsorption capacity for SO2. The steric hindrance effect of the side chains expands the interlayer spacing of the fibers, forming a mesoporous structure (pore size 2-5 nm). Glycidyl methacrylate crosslinking and epoxy group activation: The glycidyl methacrylate group (-O-CH2-CH(O)CH2) undergoes ring opening at high temperature, forming ether bonds with the hydroxyl groups on the fiber surface for crosslinking. Synergistic effect: For every 0.1-fold increase in glycidyl methacrylate content, fiber temperature resistance increases by 15℃; crosslinking density is controlled at 3.5×10 - 4 mol / cm³, balancing adsorption capacity and mechanical strength. Ammonium persulfate initiation mechanism: thermal decomposition characteristics: decomposition at 85℃ generates sulfate free radicals, which attack C-Cl bonds on the fiber surface to generate active sites. Nitrogen protection: oxygen concentration <0.5ppm, ensuring an average free radical lifetime >30min. Chain growth control: stirring rate of 150rpm ensures monomer conversion rate of over 92%, and grafting rate controlled at 35-45%. Triethylamine catalysis, epoxy ring opening: through nucleophilic attack mechanism, catalyzes the reaction of residual glycidyl ester groups with adjacent carboxylic ester groups. Network reconstruction: forming a three-dimensional interpenetrating network structure, increasing compressive strength to 18MPa. Porosity stabilizes in the 65-70% range, and BET specific surface area reaches 320m² / g. Simultaneously, tests were conducted using Example 5, such as... Figure 2 The scanning electron microscope images shown demonstrate improved thermal stability: the glass transition temperature remains at -17℃, while the thermal decomposition temperature increases from 205℃ to 230℃. Adsorption kinetics are optimized: the pseudo-second-order kinetic model shows a goodness of fit R² = 0.996, with an SO2 adsorption capacity of 135 mg / g (Langmuir model calculated value 138 mg / g). Cyclic stability is also demonstrated: after 20 regenerations, the specific surface area retention rate is >95%, and the surface functional group attenuation is <8%. This modification process, through the synergistic effects of physical swelling, chemical grafting, and topological crosslinking, constructs a composite fiber material with a hierarchical porous structure and active adsorption sites, providing an ideal adsorption medium for desulfurization of lithium mica sintering flue gas.
[0045] The above description, in conjunction with specific embodiments, provides a further detailed explanation of the present invention. It should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art of modified nanomaterials, to which this invention pertains, several simple deductions or substitutions can be made without departing from the concept of the present invention, and all such deductions or substitutions should be considered to fall within the scope of protection defined by the claims submitted herein.
Claims
1. A process for removing sulfur dioxide from sintering flue gas of lithium mica, characterized in that: Includes the following steps: 40-65 parts by weight of sodium bicarbonate, 15-30 parts by weight of slaked lime, 5-12 parts by weight of lithium sulfate, and 10-30 parts by weight of polyvinylidene chloride (PVDC) fiber are mixed evenly to obtain the adsorbent. The modification method of PVDC fiber is as follows: PVDC fiber is dispersed in 15-30 times its mass of acetone at 60-70℃ and 120-140 rpm. Then, 2-3 times its mass of methyl acrylate and 0.2-0.7 times its mass of glycidyl methacrylate are added, and the mixture is stirred and mixed at 80℃ for 24 hours. Finally, 0.05-0.15% by mass of chlorinated bicarbonate is added. Ammonium sulfate was heated to 85±2℃ under nitrogen protection and stirred at 150 rpm for 30 min. Then, 0.5-1.2% (by weight of polyvinylidene chloride fiber) of triethylamine was added, and the reaction was carried out at 120-140℃ for 2-4 h. After cooling, the adsorbent was obtained. Next, the prepared adsorbent was injected into an electrostatic agglomerator at 120-160℃ for co-agglomeration and adsorption with fly ash particles in the sintering flue gas of lepidolite. Then, the flue gas after co-agglomeration and adsorption was passed through a bag filter to adsorb residual sulfur dioxide. Finally, the adsorbent after co-agglomeration and adsorption was regenerated for recycling.
2. The process for removing sulfur dioxide from lepidolite sintering flue gas according to claim 1, characterized in that: Includes the following steps: 45-60 parts by weight of sodium bicarbonate, 20-28 parts by weight of slaked lime, 5-12 parts by weight of lithium sulfate, and 12-25 parts by weight of polyvinylidene chloride fiber are mixed evenly to obtain an adsorbent. Next, the prepared adsorbent is injected into an electrostatic agglomerator at a temperature of 130-150℃ to co-agglomerate and adsorb fly ash particles in the sintering flue gas of lepidolite. Then, the flue gas after co-agglomeration and adsorption is passed through a bag filter to adsorb residual sulfur dioxide. Finally, the adsorbent after co-agglomeration and adsorption is regenerated to obtain a regenerated adsorbent for recycling.
3. The process for removing sulfur dioxide from lepidolite sintering flue gas according to claim 2, characterized in that: Includes the following steps: 55 parts by weight of sodium bicarbonate, 24 parts by weight of slaked lime, 10 parts by weight of lithium sulfate, and 20 parts by weight of polyvinylidene chloride fiber were mixed evenly to obtain an adsorbent. Next, the prepared adsorbent was injected into an electrostatic agglomerator at 140°C to co-agglomerate and adsorb fly ash particles from lepidolite sintering flue gas. Then, the flue gas after co-agglomeration and adsorption was passed through a bag filter to adsorb residual sulfur dioxide. Finally, the adsorbent after co-agglomeration and adsorption was regenerated to obtain a regenerated adsorbent for recycling.
4. The process for removing sulfur dioxide from lepidolite sintering flue gas according to claim 1, characterized in that: The physicochemical parameters of the polyvinylidene chloride fiber are as follows: glass transition temperature: -17℃, melting temperature: 205℃, crystal density: 1.96g / cm³, fiber diameter: 0.1mm, fiber length: 2mm.
5. The process for removing sulfur dioxide from lithium mica sintering flue gas according to claim 1, characterized in that: The parameters for co-condensation are as follows: the adsorbent is injected by high-pressure injection, the pressure of which is 0.5-1.0 MPa, and the pressure source for high-pressure injection is high-pressure gas.
6. The process for removing sulfur dioxide from sintering flue gas of lithium mica according to claim 5, characterized in that: The parameters for the co-condensation are as follows: voltage: 30-40kV, current: 0.1-0.3mA / m 2 Dwell time: 1.5-2 seconds.
7. The process for removing sulfur dioxide from sintering flue gas of lithium mica according to claim 1, characterized in that: The internal relative humidity of the electrostatic agglomerator is 10-20%.
8. The process for removing sulfur dioxide from sintering flue gas of lithium mica according to claim 1, characterized in that: The regeneration process is as follows: the first stage temperature control is 450℃-480℃, maintained for 20-30 minutes; the second stage temperature control is 500℃-520℃, maintained for 15-20 minutes; and the third stage temperature control is 465℃, maintained for 10-15 minutes.
Citation Information
Patent Citations
Sorbent material for removing nitrogen oxides from indoor or cabin air
CN116322938A
Process for removing sulfur dioxide and heavy metal thallium in lepidolite sintering flue gas
CN116603385A